The Influence of Leadership and Organizational Culture on Company Performance Through Job Satisfaction (Case Study on PT. Daisy Mutiara Samudra) - Andry Kristanto; Fajar Cahyo Utomo; Samosir, Partogi Saoloan (Journal of Islamic Studies & Social Science, 2024)
Leadership and organizational culture within a company are considered important because they can influence loading and unloading activities, which are closely related to the human resource management (HRM) system and employees, particularly operational employees. Daisy Mutiara Samudra has a total of 85 operational employees, which impacts job satisfaction and company performance. Empirically, there is a relationship between job satisfaction and productivity, and the success of an organization greatly depends on the people who work within it. Therefore, employee job satisfaction plays a crucial role in determining the performance and success of an organization. This research uses an explanatory analysis approach to observe the causal relationship between exogenous variables and endogenous variables. The research results indicate that leadership and organizational culture have a positive and significant impact on employee job satisfaction at PT. Furthermore, effective leadership and a positive organizational culture can enhance comfort and satisfaction in the workplace. The research also finds that job satisfaction positively and significantly impacts PT performance, meaning that the higher the job satisfaction, the better the organization's performance. Employees who feel valued and have a supportive work environment will increase their motivation and commitment to the company. Other findings indicate that job satisfaction significantly mediates the influence of leadership on company performance.